Age-related hearing loss and balance disorders: analysis of interactions and clinical implications in older persons. Systematic review and meta-analysis - Frosolini, Andrea; Franz, Leonardo; Calvanese, Leonardo; Caragli, Valeria; Parrino, Daniela; Fabbris, Cristoforo; Badin, Giulio; Negrisolo, Michael; Cenedese, Roberta; Doretto, Lisa; Brescia, Giuseppe; de Filippis, Cosimo; et al. (Frontiers in Aging, 2026)
IntroductionAge-related hearing loss (ARHL) frequently coexists with balance disorders in older persons, but the mechanisms and rehabilitative leverage of this association remain unsettled. We synthesized evidence on interactions between ARHL and vestibular/gait dysfunction, quantified mobility and fall outcomes, and appraised clinical implications for prevention.MethodsFollowing PRISMA and a registered PROSPERO protocol, we searched PubMed (MEDLINE), Scopus and Web of Science Core Collection. Inclusion required adults ≥65 years, ARHL and quantitative vestibular/balance outcomes. Forty studies met the criteria. Vestibular pooling was infeasible due to heterogeneous designs and metrics. In quantitative analysis, continuous outcomes were meta-analysed as standardized mean differences (SMD) (Hedges g) using random effects (REML) for ARHL–control contrasts and a fixed effect for within-participant Hearing Aid (HA) ON–OFF contrasts. For falls, we pooled Odds Ratio (OR) with REML.ResultsFive out of seven studies linked ARHL to vestibular impairment. Across six studies, ARHL was associated with slower Timed Up to Go (SMD = −0.679), yet meta-regression showed systematic bias from age imbalance (−0.036 SMD per year older in HL), and the adjusted intercept was not significant. In three HA ON–OFF studies, static posturography improved with amplification (g = 0.459). The falls meta-analysis (k = 4; follow-up 12–60 months) showed higher fall odds with ARHL (OR = 1.55).DiscussionAge is a dominant driver of mobility, but ARHL contributes modifiable risk through sensory and cognitive-motor pathways. Consistent improvements with HA and converging gait data support integrating auditory rehabilitation—alongside vestibular/sensory-integration training—into multimodal fall-prevention strategies. Standardized protocols and age-balanced trials are priorities to refine effect estimates and clarify mechanisms.